Why the problem of evil undermines the problem of divine hiddenness. Issue 4 (27th July 2016) - DUMSDAY, TRAVIS
Abstract: The two most prominent arguments against theism are the problem of evil and the problem of divine hiddenness. Here I argue that if the evidential problem of evil is truly forceful, it could block the ability of God to reveal His existence in a rationally indubitable way, which would in turn undermine the evidential problem of divine hiddenness.